A New Model of Angkor Wat: Simulated Reconstruction as a Methodology for Analysis and Public Engagement. (3rd July 2017) - Chandler, Tom; McKee, Brent; Wilson, Elliott; Yeates, Mike; Polkinghorne, Martin
ABSTRACT: Since its construction in the twelfth century, Angkor Wat has endured as a pre-eminent regional, spiritual, and artistic symbol of mainland Southeast Asia. The temple has been a perennial focus of art-historical research, with scholars typically considering it as an architectural and artistic archetype and as a manifestation of a belief system. The disciplines of art history and digital visualisation, when previously brought together in relation to the temple, have presented the temple as an isolated artefact. Such static interpretations deserve to be discarded, as augmented digital visualisations that are now available offer scholars the opportunity to situate the temple within its historical landscape with goal seeking animated inhabitants (termed 'agents'), displays of religious practice, ephemeral architecture, and vegetation. Drawing upon recent archaeological findings, a team of researchers from Monash University has created a dynamic simulation of twelfth-century Angkor Wat where plural reconstructions can be explored jointly by digital practitioners and Southeast Asia specialists. In contrast to broad archaeological studies that plot change over decades or centuries, this simulation re-creates just 24 hours; a day in the life of medieval Angkor Wat.